Regional Economics: How does Tourism Influence Regional Revenue of Malang Raya? - Wahyuni, Elok Tri; Susilo, Susilo; Muljaningsih, Sri (Journal of Indonesian Tourism and Development Studies, 2018)
This paper aims to analyze the influence of tourism sector to regional revenue of Malang Raya. In this case, tourism sector used the number of tourist arrival, hotel's room occupancy rate, the number of restaurants, and the sum of PDRB (Gross Regional Domestic Product) during the period of 2006-2016. The secondary panel data from three Local Governments in Malang Raya is analyzed by using fixed effect model of multiple regressions. The result shows that all independent variables simultaneously give significant influence to regional revenue. Partially, the number of tourist arrival and hotel's room occupancy rate give the significant influence to regional revenue. The other two variables, i.e. the number of restaurant and sum of PDRB did not give significant influence. A regression model of 97.76% is generated to predict regional revenue of Malang Raya. The conclusion gives an insight that local governments in Malang Raya should pay more attention to the effort of promoting Malang Raya to encourage tourist to come and stay longer, in order to increase the regional revenue and also to increase the share of the tourism sector to regional revenue. Keywords: Malang Raya, regional revenue, tourism.